Essential neuromodulation - Arle, Jeffrey E.; Shils, Jay L. (Academic Press, 2022)
Essential Neuromodulation, Second Edition is a concise reference covering all of the basic principles of neuromodulation in a single affordable volume for neuroscientists, residents, fellows, bioengineers and basic clinical practitioners. This second edition expands on developments in the field since 2011, emphasizing essential observations from all of the important clinical phases involved in any neuromodulation: targeting, intraoperative assessment, programming, complications and complication avoidance. As neuromodulation remains an exciting and rapidly advancing field, this information is critical for neurosurgeons, neurophysiologists, bioengineers and other proceduralists.